Number of Cigarettes Smoked Per Day, Smoking Index, and Intracranial Aneurysm Rupture: A Case–Control Study - Feng, Xin; Qian, Zenghui; Zhang, Baorui; Guo, Erkang; Wang, Luyao; Liu, Peng; Wen, Xiaolong; Xu, Wenjuan; Jiang, Chuhan; Li, Youxiang; Wu, Zhongxue; Liu, Aihua (Frontiers in Neurology, 2018)
Background and purpose We aimed to investigate the effect of smoking on the risk of intracranial aneurysm (IA) rupture (IAR), specifically relationship between the number of cigarettes smoked per day (CPD) or smoking index and the risk of IAR. Methods We performed a single-center case–control study of consecutive patients evaluated or treated for IA at our institution from June 2015 to July 2016. Cases were patients with a ruptured IA. Two age- and sex-matched controls with an unruptured IA were included per case. Conditional logistic regression models were used to assess the relationship between both the CPD and smoking index (CPD × years of smoking) and IAR. Results The study population included 127 cases of IAR and 254 controls. The higher IAR risk was associated with cigarette smoking (both current and former) (OR, 2.3; 95% CI, 1.1–4.8; P = 0.029). Our subgroup analysis of smokers revealed a significant association between IAR risk and current smoking (OR, 2.8; 95% CI, 1.2–6.3; P = 0.012), current heavy smoking (CPD ≥ 20) (OR, 3.9; 95% CI, 1.4–11.0; P = 0.007), and a smoking index ≥800 (OR, 11.4; 95% CI, 2.3–24.5; P = 0.003). Former smoking was not significantly associated with IAR (OR, 1.1; 95% CI, 0.3–4.0; P = 0.929). Conclusion A dose–response relationship has been noted for intensity and duration of smoking consumption and increased risk of IAR. As smoking is modifiable, this finding is important to managing patients with IAs to quit or reduce smoking prior to life-threatening subarachnoid hemorrhage.